The importance of serotonin in the gastrointestinal tract - Koza, Jarosław; Kwiatkowska, Renata; Jurgoński, Adam; Pujanek, Małgorzata; Ameryk, Monika; Sikorski, Piotr; Meder, Agnieszka; Świątkowski, Maciej (Journal of Education, Health and Sport, 2017)
Introduction. Serotonin also called as 5-hydroxytryptamine (5-HT) is a very important neurotransmitter in the central nervous system, also plays an important role in the gastrointestinal tract. It is known that the basis of the peristaltic reflex in the gut is the result of serotonin release from enterochromaffin cells. The vast majority of serotonin in the human body is associated with the gastrointestinal tract. It is produced by enterochromaffin cells, the activation of which causes the serotonin secretion into the intercellular space and its active action through the receptors. There are seven main types of serotonin receptors and some of them have also subtypes. Description of the current knowledge and conclusions. Serotonin is responsible for some symptoms of carcinoid syndrome. It is the result of higher 5-hydroxytryptamine content in the body. Moreover disrupted serotonin system is found in different gastrointestinal disorders e.g. in gastroesophageal reflux disease, functional heartburn, hypersensitive esophagus, functional dyspepsia, irritable bowel syndrome (both diarrhoea predominant and constipation predominant) as well as in inflammatory bowel diseases. Knowledge of changed mechanisms in particular diseases facilitates the optimal choice of treatment. Drugs affecting the serotonin system in gastroenterological clinical practice are useful especially in the case of abnormalities in the brain - gut axis.